2007
DOI: 10.1590/s0004-282x2007000100037
|View full text |Cite
|
Sign up to set email alerts
|

Dandy-Walker syndrome in adult mimicking myasthenia gravis

Abstract: -The Dandy-Walker syndrome (DWS) is a rare posterior fossa malformation. The DWS can occur associated with other brain or systemic malformations, but ocular abnormalities in this disease are rare and clinical findings mimicking myasthenia gravis have not been described to date. We report a 23-yearold woman who presented mild limitation of the ocular movements with progressive palpebral ptosis, which changed in intensity during the day. The investigation showed negative anti-acetylcholine receptor antibody, rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 16 publications
0
13
0
4
Order By: Relevance
“…[7] Various predisposing factors were reported such as infections, cranial trauma, chronic disturbance in cerebrospinal fluid pressure, persistence of embryonic tissue, vascular lesions, teratogens, rubella, alcohol and maternal diabetes. [2] In the present case, cranial trauma could have been the responsible factor.…”
Section: Discussionmentioning
confidence: 68%
“…[7] Various predisposing factors were reported such as infections, cranial trauma, chronic disturbance in cerebrospinal fluid pressure, persistence of embryonic tissue, vascular lesions, teratogens, rubella, alcohol and maternal diabetes. [2] In the present case, cranial trauma could have been the responsible factor.…”
Section: Discussionmentioning
confidence: 68%
“…Rarely, there are no significant symptoms, and diagnosis occurs later or in older adulthood. Scattered case studies of this phenomenon are reported in the literature (Cardoso, Lange, Lorenzoni, Scola, & Werneck, 2007; Engelhard & Meyer, 1995; Forestier et al, 2008; Venturini, Magni, Pucci, & Mazzinghi, 2009; Warwick, Reyes, Ayoob, & Subit, 2008). Generally, the cause of Dandy‐Walker Malformation or Dandy‐Walker Variant is unknown.…”
Section: Dandy‐walker Malformation and Variantmentioning
confidence: 99%
“…6 Literature suggests that 40% individuals with DWM were normal intellectuals while 40% had mental retardation and 20% were borderline. 7 It is said that clinical examination cannot replace any modalities of investigation. In DWM, there are many signs or symptoms, none of these are characteristic to diagnose individual as DWM and diagnosis is solely based on imaging techniques, usually computed tomography (CT scan) or magnetic resonance imaging (MRI) of brain.…”
Section: Introductionmentioning
confidence: 99%